The Transformation of Pesantren Education from the New Order to the Reform Era in Terms of Curriculum, Methods, and Islamic Educational Identity - Yusra Dewi Siregar (Fitrah: Journal of Islamic Education, 2026)
The transformation of pesantren education cannot be separated from the pressures of educational policies during the New Order era, which emphasized standardization, depoliticization, and integration into the national education system, thereby potentially reducing institutional autonomy and the distinctiveness of Islamic scholarly traditions. In the Reformasi era, socio-political changes and globalization have further required pesantren to adapt more dynamically. This study aims to analyze how pesantren respond to these changes and their implications for curriculum, teaching methods, and Islamic educational identity. This research employs a qualitative historical approach through document analysis, policy review, and secondary literature. The findings reveal that pesantren function as adaptive and reflective educational actors through strategies of selective adaptation. This transformation has led to the emergence of a hybrid educational model that integrates Islamic intellectual traditions with the demands of modern education. These changes are not linear, but rather represent a process of negotiation between tradition, state policy, and global developments. The implications of this study highlight the importance of granting greater autonomy to pesantren, as well as the relevance of the hybrid model in developing Islamic education that balances tradition and modernity.